Sosialisasi Hastabrata: Teori Kepemimpinan Jawa untuk LDKS OSIS di UPTD SMP Negeri 5 Depok - Puri Kurniasih (Darma Cendekia, 2025)
Socialization is a process of learning and teaching humans to study the sociocultural environment of a society. Delivering a material that is based on the social culture of a particular community is part of the socialization process. The student council of SMP Negeri 5 Depok, under the UPTD Depok City, has implemented a series of LDKS. One of the series of activities was socialization about Javanese leadership theory, also known as hastabrata. Participants in this socialization were students and teachers of the Student Council Supervisor of SMP Negeri 5 Depok. Hastabrata is a Javanese leadership theory with philosophical value. As part of the social culture in Javanese island society, it is good for students from adolescence to know Javanese leadership theory so that, in addition to understanding global leadership theory, students also have knowledge of local leadership theory. The socialization will be held on Friday, November 24, 2023, in the school hall of SMP Negeri 5 Depok. In the implementation process, students and teachers listened to material about the understanding of leadership, the difference between leaders and bosses, global and local leadership theory, the description of hastabrata as one of the local leadership theories, and applying hastabrata theory in student council leadership. Students engage interactively to apply hastabrata theory in leadership, especially in the student council environment. The attention and appreciation from students and teachers at SMP Negeri 5 Depok were extraordinary and warm.